GE_GERICHTE P/6569/2024 vom 1. Dezember 2025 - GE Cour de justice (2025)
NOTIFICATION DE LA DÉCISION;RESTITUTION DU DÉLAI;DÉCISION D'IRRECEVABILITÉ;FRAIS(EN GÉNÉRAL) | CPP.399; CPP.85; CPP.82.al2.letb; CPP.84.al4; CPP.94; CPP.388.al2.leta; CPP.428